Development and Characterization of a Reverse Genetics System for a Human-Derived Severe Fever With Thrombocytopenia Syndrome Virus Isolate From South Korea - Yun, Seok-Min; Lee, Tae-Young; Lim, Hee-Young; Ryou, Jungsang; Lee, Joo-Yeon; Kim, Young-Eui (Frontiers in Microbiology, 2021)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging, tick-borne Bandavirus that causes lethal disease in humans. As there are no licensed vaccines and therapeutics for SFTSV, there is an urgent need to develop countermeasures against it. In this respect, a reverse genetics system is a powerful tool to help achieve this goal. Herein, we established a T7 RNA polymerase-driven reverse genetics system to rescue infectious clones of a Korean SFTSV human isolate entirely from cDNA. To establish this system, we cloned cDNAs encoding the three antigenomic segments into transcription vectors, with each segment transcribed under the control of the T7 promoter and the hepatitis delta virus ribozyme (HdvRz) sequences. We also constructed two helper plasmids expressing the nucleoprotein (NP) or viral RNA-dependent RNA polymerase (RdRp) under the control of the T7 promoter and the encephalomyocarditis virus (EMCV) internal ribosome entry site (IRES). After co-transfection into BHK/T7-9 cells with three transcription and two helper plasmids, then passaging in Vero E6 or Huh-7 cells, we confirmed efficient rescue of the recombinant SFTSV. By evaluating the in vitro and in vivo virological properties of the parental and rescued SFTSVs, we show that the rescued virus exhibited biological properties similar to those of the parental virus. This system will be useful for identifying molecular viral determinants of SFTSV infection and pathogenesis and for facilitating the development of vaccine and antiviral approaches.